P2.133 Plasma Cell Balanitis (PCB). A Clinico-Pathologic Study of 132 Cases. (13th July 2013) - Kumar, B
Abstract : Bhushan Kumar, Tarun Narang, B.D. Radotra Background: PCB also knows as Zoon balanitis, is a benign asymptomatic but chronic and erosive inflammatory condition of glans penis and prepuce that generally affects uncircumcised men in later years. Clinical presentation involves usually a single, shiny, well defined reddish patch. Disease may persist for years which adversely affects the quality of life of the individuals. Methods: 132 patients with a clinical diagnosis of PCB were studied between 2001–2010. Biopsy was done in patients who agreed for the procedure. Patients who did not agree for circumcision were prescribed fluticasone cream or tacrolimus 0.1% and were followed up. Results: The age of the patients ranged from 24–70 years. Majority of patients had symptoms for more than 6 months. Lesions involved prepuce and glans in majority of patients; 82 (62.12%), prepuce only in 24 (18.18%) and glans only in 26(19.69%). Tissue for histopathology was available in 115 patients. Histologically, epidermal edoema, a dense upper dermal band of chronic inflammatory cells, including many plasma cells, dilated capillaries, extravasated red blood cells and hemosiderin deposition, were seen. In all the 115 cases PCB was successfully treated by circumcision. Remaining patients were treated with fluticasone or tacrolimus 0.1%. The period of follow up ranged from 2–7 years. Circumcised patients did not develop any recurrences. However the patients treated with fluticasone and tacrolimus had a course of relapses and remissions. Only one patient developed erythroplasia of Query at during the follow up. Conclusions: PCB is a benign condition, with characteristic clinical and histopathological features. Although various treatment modalities have been used, circumcision remains the treatment of choice. PCB is an expression of dysfunctional foreskin, moreover the curative effect of circumcision in 100% of our patients suggests that it is a non-specific reactive balanitis caused by a disturbed "preputial-ecology.